2003
DOI: 10.1002/ab.10047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence estimation of school bullying with the Olweus Bully/Victim Questionnaire

Abstract: The key aim of the present research was to study the “functionality” of two global variables in the Olweus Bully/Victim Questionnaire and to examine the appropriateness of different cutoff points of these variables for prevalence estimation. Several empirical and conceptual analyses strongly attested to the functionality of the two selected variables in terms of construct validity and selected measurement properties. Similarly, a number of analyses indicated that (having been bullied/having bullied other stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
1,165
12
111

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,348 publications
(1,327 citation statements)
references
References 62 publications
39
1,165
12
111
Order By: Relevance
“…We used three measures to assess bullying, each containing one bullying-item (it has been shown that bullying can be reliably assessed using one item for bullying behavior, Solberg and Olweus 2003).…”
Section: Methodsmentioning
confidence: 99%
“…We used three measures to assess bullying, each containing one bullying-item (it has been shown that bullying can be reliably assessed using one item for bullying behavior, Solberg and Olweus 2003).…”
Section: Methodsmentioning
confidence: 99%
“…In his early research, Olweus (1978Olweus ( , 1993 distinguished between children who bully others and those who both bully others and are victimized. These "bully victims" have been characterized as hyperactive, impulsive, and as experiencing more peer rejection, more academic difficulties, and more stressful and harsh home environments (see Schwartz, Proctor, & Chien, 2001), but represent only a small portion (1% to 12%) of students (Dulmus et al, 2006;Nansel et al, 2001;Solberg & Olweus, 2003;Spriggs, Iannotti, Nansel, & Haynie, 2007). Over the past four decades, research has also shown that many bullies are socially intelligent (Björkqvist, Österman, & Kaukiainen, 2000;Sutton, Smith, & Swettenham, 1999a, 1999b and enjoy considerable status in the peer group (Vaillancourt et al, 2003), leading to distinctions between socially marginalized and socially integrated bullies (Farmer et al, 2010).…”
Section: Different Types Of Bulliesmentioning
confidence: 99%
“…There are also similarities regarding age and sex variations. As with peer bullying 53,54 , incidence of sibling victimisation and bullying perpetration shows some decline with age, particularly in physical aggression 1,6,49 , and males are more likely to perpetrate acts of sibling aggression, although there are no clear gender differences in regards to victimisation 1,35,44,55 . While these characteristics show individual associations, the sex and age composition of the sibling relationship can have a significant impact on overall rates, with more sibling bullying reported in male-male 30 or older male-younger female sibling dyads 55 .…”
Section: Prevalencementioning
confidence: 99%